2002
DOI: 10.1038/nature01276
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dendritic spine stability in the adult cortex

Abstract: The structural dynamics of synapses probably has a crucial role in the development and plasticity of the nervous system. In the mammalian brain, the vast majority of excitatory axo-dendritic synapses occur on dendritic specializations called 'spines'. However, little is known about their long-term changes in the intact developing or adult animal. To address this question we developed a transcranial two-photon imaging technique to follow identified spines of layer-5 pyramidal neurons in the primary visual corte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
924
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,123 publications
(986 citation statements)
references
References 28 publications
57
924
3
2
Order By: Relevance
“…1). 21 In addition, this study also showed that in mice between 1 to 3 months of age, the rate of spine elimination is significantly higher than that of spine formation, leading to a net loss of spines during young adolescence. These results suggest that a significant percentage of spines in the mature adult mouse primary visual cortex can last throughout the lifespan of an animal and thus could provide a structural basis for lifelong information storage.…”
Section: Imaging Synaptic Structural Plasticity In the Young And Adulsupporting
confidence: 56%
See 1 more Smart Citation
“…1). 21 In addition, this study also showed that in mice between 1 to 3 months of age, the rate of spine elimination is significantly higher than that of spine formation, leading to a net loss of spines during young adolescence. These results suggest that a significant percentage of spines in the mature adult mouse primary visual cortex can last throughout the lifespan of an animal and thus could provide a structural basis for lifelong information storage.…”
Section: Imaging Synaptic Structural Plasticity In the Young And Adulsupporting
confidence: 56%
“…In particular, the advent of Green Flourescent Protein (GFP) and its spectral variants and the ability to generate transgenic mice or viral vectors to drive the expression of such proteins in specific cell types in the nervous system [17][18][19] are allowing for long-term imaging of individual synaptic structures at high resolution in living animals. 18,[20][21][22][23] The other major technical advance relates to better instrumentation for optical imaging of living tissues. Specifically, two-photon microscopy (TPM) has dra-matically enhanced the ability of deep tissue imaging.…”
Section: Introductionmentioning
confidence: 99%
“…6c). Filopodia are the telltale sign of spinogenesis, they are abundant during the critical period and disappear during circuitry maturation 25 . The density of filopodia in the adult control mice was only 0.016 ± 0.013 mm À 1 (s.d.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological plasticity of dendritic spines tightly correlates with the level of cortical plasticity 23,24 . Indeed, during circuitry maturation, dendritic spines exhibit spontaneous motility and the formation of filopodial protusions heralds the emergence of novel excitatory synapses 25 . Later on, as the circuitry reaches its adult form, filopodia become very rare, spine motility subsides and connectivity stabilizes.…”
mentioning
confidence: 99%
“…Dendritic spines form the synaptic contacts of cortical pyramidal neurons. These are mostly stable in the adult cortex [60,61], although they remodel in response to loss of afferent inputs or learning [62][63][64]. After stroke, there is initially a net loss of dendritic spines in peri-infarct cortex in the first week after stroke [52,65].…”
Section: Radial Stroke: Tissue Reorganizationmentioning
confidence: 99%